Transplantation of storm-generated coral fragments to enhance Caribbean coral reefs: A successful method but not a solution - Virginia H. Garrison; Greg Ward (Revista de Biología Tropical, 2012)
In response to dramatic losses of reef-building corals and ongoing lack of recovery, a small-scale coral transplant project was initiated in the Caribbean (U.S. Virgin Islands) in 1999 and was followed for 12 years. The primary objectives were to (1) identify a source of coral colonies for transplantation that would not result in damage to reefs, (2) test the feasibility of transplanting storm-generated coral fragments, and (3) develop a simple, inexpensive method for transplanting fragments that could be conducted by the local community. The ultimate goal was to enhance abundance of threatened reef-building species on local reefs. Storm-produced coral fragments of two threatened reef-building species [Acropora palmata and A. cervicornis (Acroporidae)] and another fast-growing species [Porites porites (Poritidae)] were collected from environments hostile to coral fragment survival and transplanted to degraded reefs. Inert nylon cable ties were used to attach transplanted coral fragments to dead coral substrate. Survival of 75 reference colonies and 60 transplants was assessed over 12 years. Only 9% of colonies were alive after 12 years: no A. cervicornis; 3% of A. palmata transplants and 18% of reference colonies; and 13% of P. porites transplants and 7% of reference colonies. Mortality rates for all species were high and were similar for transplant and reference colonies. Physical dislodgement resulted in the loss of 56% of colonies, whereas 35% died in place. Only A. palmata showed a difference between transplant and reference colony survival and that was in the first year only. Location was a factor in survival only for A. palmata reference colonies and after year 10. Even though the tested methods and concepts were proven effective in the field over the 12-year study, they do not present a solution. No coral conservation strategy will be effective until underlying intrinsic and/or extrinsic factors driving high mortality rates are understood and mitigated or eliminated. Rev. Biol. Trop. 60 (Suppl. 1): 59-70. Epub 2012 March 01. En respuesta a la dramática pérdida de corales constructores de arrecifes y la continua falta de recuperación, un proyecto de pequeña escala de transplante de corales, al cual se le dio seguimiento por 12 años, se inició en el Caribe (Islas Vírgenes de EUA) en 1999. Los principales objetivos fueron (1) identificar fuentes de colonias de coral para el trasplante, que no produjeran daños a los arrecifes, (2) evaluar la viabilidad del trasplante de fragmentos de coral generados por tormentas, y (3) desarrollar un método simple y barato para transplantar fragmentos que pudiera ser realizado por la comunidad local. La meta última era aumentar la abundancia de especies constructoras de arrecife amenazadas en los arrecifes locales. Fragmentos de coral producidos por tormenta de dos especies constructoras de arrecife amenazadas [Acropora palmata y A. cervicornis (Acroporidae)] y otras especies de crecimiento rápido [Porites porites (Poritidae)] fueron recolectadas en ambientes no adecuados para la supervivencia de fragmentos de coral y se trasplantaron a los arrecifes degradados. Fajitas de nylon inerte fueron utilizadas para unir los fragmentos de corales transplantados al sustrato de coral muerto. La sobrevivencia de 75 colonias de referencia y de 60 transplantadas fueron monitoreadas por más de 12 años. Sólo el 9% de las colonias estaban vivas tras 12 años, sin presencia de A. cervicornis, el 3% de los transplantes de A. palmata y el 18% de las colonias de referencia de Acropora. El 13% de los transplantes de P. porites y el 7% de las colonias de referencia sobrevivieron. El desprendimiento físico resultó en la pérdida del 56% de las colonias, mientras que el 35% murió en el lugar. Solamente A. palmata mostró una diferencia en sobrevivencia entre los trasplantes y las colonias de referencia, eso fue solo en el primer año. La ubicación fue un factor en la sobrevivencia sólo para las colonias de referencia de A. palmata y después de 10 años. A pesar de que los métodos y los conceptos fueron probados efectivamente en el campo por más de 12 años de estudio, no mostraron ser la solución. Ninguna estrategia de conservación va a ser efectiva hasta que se delimiten y sean entendidos, mitigados o eliminados los factores intrínsecos y/o extrínsecos que conducen a las altas tasas de mortalidad.